Pengembangan Modul dan Jobsheet Instalasi Motor Listrik Berbasis Project Based Learning Di SMKN 1 Cinangka - Idris Shuhada; Mohammad Fatkhurrokhman; Endi Permata (Peneliti.net, 2023)
The purpose of R&D research is to produce learning media products in the form of PJBL-based IML modules and jobsheets, to determine the level of expert feasibility, practicality and effectiveness in PJBL-based learning to determine whether the products made are suitable for use in learning so as to facilitate students in the learning process. The research method used is the Hannafin & Peck development model which has 3 stages of needs analysis, design, development and implementation. The results showed that the level of feasibility of the module material and IML jobsheets based on the assessment of material experts averaged 0.78 in the